ANTIOXIDANT RESPONSES OF RAINBOW TROUT (Oncorhynchus mykiss) GILLS AFTER EXPOSURE TO HYDROGEN PEROXIDE - Seker, Engin; Ispir, Unal; Yonar, Serpil Mise; Yonar, M. Enis; Turk, Cebrahil (Parlar Scientific Publications (P S P), 2015)
We evaluated antioxidant responses of Oncorhynchus mykiss, experimentally exposed to different concentrations of hidrogen peroxide (H2O2). Different concentrations of H2O2 (50 and 100 ppm) were administrated to the fish for 30, 60 and 90 min. Samples of the gill were collected at the end of the experiment, and analysed for their oxidant antioxidant status, including the malondialdehyde (MDA) level, the catalase (CAT) and glutathione peroxidase (GSH-Px) activity as well as the reduced glutathione (GSH) concentration. Results obtained showed that H2O2 significantly increased MDA level. Compared to controls, GSH level and GSH-Px and CAT activities were significantly reduced in the fish that were exposed to different concentrations of H2O2. The current data suggest that H2O2 has an oxidative-stress-inducing potential in fish. The various parameters studied in this investigation can also be used as biomarkers of exposure to H2O2.
Keywords: Hydrogen peroxide; H2O2; rainbow trout; oxidative stress; antioxidant system